2021
DOI: 10.1016/j.celrep.2021.109490
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PHLPP1/2 phosphatases rescues pancreatic β-cells in diabetes

Abstract: Highlights d PHLPP1/2 are highly elevated in metabolically stressed b cells in diabetes d Metabolic-stress-induced mTORC1 hyper-activation leads to PHLPP upregulation d PHLPPs regulate b-cell survival-dependent kinases AKT and MST1 d PHLPP inhibition restores glycemia, b-cell survival, and function

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 96 publications
(136 reference statements)
0
15
0
Order By: Relevance
“…Following up on our and other studies ( Alamuru et al., 2014 ; Behera et al., 2018 ; Katsenelson et al., 2019 ; Lupse et al., 2021 ), in the current study, we explored the importance of PHLPP1 in the development of foam cells. We observed that lipid accumulation in foam cells in vitro was substantially reduced upon the depletion of PHLPP1 in RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 92%
“…Following up on our and other studies ( Alamuru et al., 2014 ; Behera et al., 2018 ; Katsenelson et al., 2019 ; Lupse et al., 2021 ), in the current study, we explored the importance of PHLPP1 in the development of foam cells. We observed that lipid accumulation in foam cells in vitro was substantially reduced upon the depletion of PHLPP1 in RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 92%
“…Yuan et al [ 46 ] revealed that LATS2 acts as a key upstream activator for the mTORC1 pathway in β cells exposed to stress and that the knockout of Hippo kinase was significant for weakening downstream signaling, including that of mTORC1. The arrest of the mTORC1 pathway was revealed by the blocking of β cell apoptosis, which clearly showed that the pro-apoptotic effect of LATS2 is mTORC1-dependent and is over-activated by LATS2 in diabetes in INS-1E cells and human pancreatic islets [ 13 ]. The development of apoptosis in β cells and isolated human pancreatic islets grown under pro-apoptotic (glucotoxicity) conditions revealed the implementation of mTORC1 in a LATS2-dependent manner.…”
Section: Core Proteins Of the Hippo Pathway As A Therapeutic Target In Diabetesmentioning
confidence: 99%
“…β cell dysfunction and worsening insulin resistance over time lead to deterioration of glycemic control and, as a result, need for more intensive pharmacotherapy [ 9 , 10 ]. Over time, this is usually manifested by a complete inability of the endogenous islet resulting from a loss of β cells [ 10 , 11 , 12 ], which also includes impaired proliferation and dedifferentiation [ 13 , 14 ]. The metabolic stress observed in type 2 diabetes can induce the pro-inflammatory cytokines, tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6), activating a series of complex processes leading to apoptotic death of pancreatic β cells [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found the Pleckstrin homology domain leucine-rich repeat protein phosphatases 1 and 2 (PHLPP1, PHLPP2) highly upregulated in β-cells under a diabetic environment [ 2 ] and this directly correlates with β-cell death and impaired insulin secretion in human and rodent pancreatic β-cells in vitro and in vivo [ 2 , 3 ]. PHLPP1/2 are members of the protein phosphatases metal-dependent (PPM) group of serine-threonine phosphatases (STPs) family and key mediators of pro-apoptotic signaling [ 4 ].…”
mentioning
confidence: 99%
“…PHLPP1/2 are members of the protein phosphatases metal-dependent (PPM) group of serine-threonine phosphatases (STPs) family and key mediators of pro-apoptotic signaling [ 4 ]. They directly dephosphorylate and inhibit pro-survival kinase AKT together with dephosphorylation and activation of pro-apoptotic MST1 [ 2 , 4 ]; both pathways independently mediate β-cell failure [ 5 , 6 ].…”
mentioning
confidence: 99%